ANALISIS PENGARUH PROFITABILITAS, STRUKTUR ASET, LIKUIDITAS, DAN PERTUMBUHAN PENJUALAN TERHADAP STRUKTUR MODAL - Habibah, Maulia; Andayani, Andayani (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
Basically, every company requires capital in order to finance their operational activity and to expand their business so capital becomes one of the important elements in a company.When the capital which is owned by the company is large the operational activity that can be conducted is large as well.The purpose of this research is to analyze the influence of profitability, assets structure, liquidity and sales growth to the companyâs capital structure. The population is consumer goods industry companies. The sample collection technique has been done by using purposive sampling and 16 companies which meet the criteria have been selected as the research samples. The multiple regressions analysis is used as the analysis technique.The result of the test shows that from four variables which have been used as the research models i.e.: profitability, assets structure, liquidity and sales growth, only profitability, asset structure, and liquidity variables have significant influence to the capital structure of consumer goods industry companies.Keywords:Profitability, Asset Structure, Liquidity, Sales Growth, Capital Structure.